Inter-domain traffic routing in vehicular delay tolerant networks - Farahmand, Farid (2010)
In this paper, we consider the problem of dynamic inter-domain traffic routing between a VDTN and a non-DTN (e.g., Internet). The inter-domain traffic can be classified as inbound and outbound traffic. Our main contribution in this work is the intro- duction of several fault-tolerant routing algorithms for inbound and outbound traffic. Using simulations, we compare the performance of the proposed algorithms in terms of required resources, packet delivery time, and blocking probability.